2020
DOI: 10.3390/electronics9020238
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Flexibility of the Interconnects on the Dynamic Bending Reliability of Flexible Hybrid Electronics

Abstract: The growing interest towards thinner and conformable electronic systems has attracted significant attention towards flexible hybrid electronics (FHE). Thin chip-foil packages fabricated by integrating ultra-thin monocrystalline silicon integrated circuits (ICs) on/in flexible foils have the potential to deliver high performance electrical functionalities at very low power requirements while being mechanically flexible. However, only very limited information is available regarding the fatigue or dynamic bending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Vanfleteren et al reported an ultra-thin microcontroller (thickness: 20 µm) that performed on a flexible substrate at a curvature radius of 3.3 mm [12,13]. Also, K. Bock group reported roll-to-roll process and chip-foil packaging using ultra-thin silicon chips [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Vanfleteren et al reported an ultra-thin microcontroller (thickness: 20 µm) that performed on a flexible substrate at a curvature radius of 3.3 mm [12,13]. Also, K. Bock group reported roll-to-roll process and chip-foil packaging using ultra-thin silicon chips [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic bending reliability (fatigue) of such ICs is quite important. Palavesam et al found that gold has better fatigue performance compared to copper and aluminum [ 73 ].…”
Section: Flexible Interconnectsmentioning
confidence: 99%
“…The authors also produced contact pads compatible with 6-pin zero insertion force (ZIF) connectors commonly used in printed circuit boards for portable and wearable electronics. [40,41] The PET test pattern configuration is depicted in Figure 1. Additional details can be found in the Supporting Information.…”
Section: Fabrication Of Plastic Rgo Lgtsmentioning
confidence: 99%